GUI Based Control System Analysis using PID Controller for Education - Ashwaq Abdulameer; Marizan Sulaiman; M.S.M. Aras; Dawood Saleem (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
PID control strategy should be understood as a huge part in the education oriented on process control. Application of suitable GUI windows software can contribute in the increase of education quality and providing a better understanding of PID control through as it provides a user friendly environment which is suitable and comfortable for teaching, learning and training application. This paper present the PID control system analysis by explaining the PID controller three-term parameters, PID control types and structure, and PID tuning approach using Ziegler-Nichols and manual tuning method (in both s-domain and z-domain) with the help of simulation and Graphical User Interface GUI windows based on MATLAB. This software package is targeted for engineering students and practicing engineers.